SOCIAL-PSYCHOLOGICAL FACTORS OF AGGRESSIVENESS IN ADOLESCENCE - Arakulov , Gayrat (Scientific practical conference, 2026)
This article analyzes the socio-psychological factors influencing the manifestation of aggression in adolescents. Family environment, peer groups, media exposure, and individual psychological characteristics are considered as key determinants of aggressive behavior. Strategies for reducing and preventing aggression are also discussed.